Epidemiological Peculiarities and Clinical Features of Ebola Virus Disease in the Republic of Guinea - V. V. Maleev; Facely Tolno; K. Victor Konomou; Thierno Idy Sow; Ya. Yu. Itskov; Yu. V. Demina; A. E. Levkovsky; E. V. Kolomoets; G. A. Kovalev; V. Yu. Khoroshilov; Z. M. Omariev (Проблемы особо опасных инфекций, 2015)
The current outbreak of the Ebola fever in West Africa is unprecedented in terms of its scale. As of today, 27550 suspected cases and 11235 deaths have been reported. The outbreak differs from previous epidemics in terms of epidemiological and clinical progression of the disease. The article covers several epidemiological issues related to Ebola virus disease by the example of the Guinean outbreak, which has been plaguing the country since 2014. Given is the preliminary clinical analysis of the medical observations, performed in the Research and Diagnostic Centre of Epidemiology and Microbiology built by RUSAL. Regarded are epidemiological and clinical features of the Ebola virus disease (EVD) in 83 patients, who were admitted to RUSAL Treatment Center since March 6th till June 30th, 2015. In 28 of the patients, EVD diagnosis was laboratory confirmed. The principle assessment criteria are: morbidity rate, lethality index, gender, age, occupation, time since the onset of the disease until hospitalization, an average duration of the stay at the hospital, complaints, symptoms, complications, and the therapy provided.